2011
DOI: 10.1364/oe.19.015990
|View full text |Cite
|
Sign up to set email alerts
|

Higher order modes in photonic crystal slabs

Abstract: We present a detailed investigation of higher order modes in photonic crystal slabs. In such structures the resonances exhibit a blue-shift compared to an ideal two-dimensional photonic crystal, which depends on the order of the slab mode and the polarization. By fabricating a series of photonic crystal slab photo detecting devices, with varying ratios of slab thickness to photonic crystal lattice constant, we are able to distinguish between 0th and 1st order slab modes as well as the polarization from the shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The confinement in the z -direction induces a blue-shift of the photonic crystal modes. Compared with the fundamental mode, the confinement of higher order modes is weaker and the blue-shift is stronger 32 . In our structure, only the fundamental 0th order modes and the 1st order modes overlap in frequency with our photodetector absorption.…”
Section: Resultsmentioning
confidence: 98%
“…The confinement in the z -direction induces a blue-shift of the photonic crystal modes. Compared with the fundamental mode, the confinement of higher order modes is weaker and the blue-shift is stronger 32 . In our structure, only the fundamental 0th order modes and the 1st order modes overlap in frequency with our photodetector absorption.…”
Section: Resultsmentioning
confidence: 98%
“…When the broadband source is used, a fundamental waveguide mode appears at the wavelength of 561.5 nm, in addition to the higher order waveguide modes, which appear between the wavelengths of 200 nm and 300 nm, as shown in Figure 5 a. These higher order modes are basically generated by the confinement of the photons within the slab waveguide, forming subbands in the structure [ 39 ]. However, it has been demonstrated that when a higher order mode is located near the peak wavelength of the fundamental mode, the intensities of both the fundamental and the higher order mode rise upon the increase of the pump power, reducing the efficiency of the fundamental mode [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…13 Another way to change the resonance frequency by a factor n is scaling the whole structure by n. This remarkable property is due to the scale invariance of Maxwell's equations. Using these two methods, it is possible to obtain a variety of PCS that all exhibit the chosen PCS mode at the same frequency.…”
Section: Simulationmentioning
confidence: 99%